2014
DOI: 10.1038/mt.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Against Mannose-capped Lipoarabinomannan Inhibits Virulent Mycobacterium tuberculosis Infection in Mice and Rhesus Monkeys

Abstract: The major surface lipoglycan of Mycobacterium tuberculosis (M. tb), mannose-capped lipoarabinomannan (ManLAM), is an immunosuppressive epitope of M. tb. We used systematic evolution of ligands by exponential enrichment (SELEX) to generate an aptamer (ZXL1) that specifically bound to ManLAM from the virulent M. tb strain H37Rv. Aptamer ZXL1 had the highest binding affinity, with an equilibrium dissociation constant (Kd) of 436.3 ± 37.84 nmol/l, and competed with the mannose receptor for binding to ManLAM and M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 38 publications
0
54
0
1
Order By: Relevance
“…Because of their high affinity and specificity, aptamers have been used as therapeutic or diagnostic tools in numerous investigations . In our previous studies, we generated the ssDNA aptamer ZXL1 specifically against ManLAM from virulent Mtb H37Rv and the ssDNA aptamer BM2, which specifically binds to ManLAM from Mycobacterium bovis (termed BCG), based on the different structures of ManLAMs in different Mycobacteria . We reported that ZXL1 competes with the MR for binding to ManLAM and inhibits ManLAM‐induced immunosuppression of DCs and that BM2 promotes M1 macrophage polarization .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their high affinity and specificity, aptamers have been used as therapeutic or diagnostic tools in numerous investigations . In our previous studies, we generated the ssDNA aptamer ZXL1 specifically against ManLAM from virulent Mtb H37Rv and the ssDNA aptamer BM2, which specifically binds to ManLAM from Mycobacterium bovis (termed BCG), based on the different structures of ManLAMs in different Mycobacteria . We reported that ZXL1 competes with the MR for binding to ManLAM and inhibits ManLAM‐induced immunosuppression of DCs and that BM2 promotes M1 macrophage polarization .…”
mentioning
confidence: 99%
“…In our previous studies, we generated the ssDNA aptamer ZXL1 specifically against ManLAM from virulent Mtb H37Rv and the ssDNA aptamer BM2, which specifically binds to ManLAM from Mycobacterium bovis (termed BCG), based on the different structures of ManLAMs in different Mycobacteria . We reported that ZXL1 competes with the MR for binding to ManLAM and inhibits ManLAM‐induced immunosuppression of DCs and that BM2 promotes M1 macrophage polarization . However, we do not know the effects of ZXL1 on macrophages or the exact nature of the cellular signaling pathway triggered by anti‐ManLAM aptamers.…”
mentioning
confidence: 99%
“…Our group has selected several aptamers specifically binding to M. tb whole cells 18 and surface lipoglycan. [19][20][21] We first implemented whole-cell SELEX and generated ssDNA aptamer NK2, which binds to virulent M. tb H37Rv with high affinity and specificity. 18 We then selected ssDNA aptamer ZXL1, which specifically binds to ManLAM from virulent M. tb strain H37Rv, 19 , 21 and significantly reduces the progression of M. tb H37Rv infections as well as bacterial loads in mice and rhesus monkeys.…”
Section: α-Toxinmentioning
confidence: 99%
“…18 We then selected ssDNA aptamer ZXL1, which specifically binds to ManLAM from virulent M. tb strain H37Rv, 19 , 21 and significantly reduces the progression of M. tb H37Rv infections as well as bacterial loads in mice and rhesus monkeys. 19 Based on the different structures of ManLAM among different Mycobacteria , we next selected ssDNA aptamer BM2 that specifically binds to ManLAM from BCG. 20 Aptamer BM2 acts as an adjuvant enhancing immunoprotective effects of BCG against virulent M. tb infection in murine and monkey models.…”
Section: α-Toxinmentioning
confidence: 99%
“…Аналогичный 16-недельный эксперимент с макаками-резусами показал меньшую эффективность терапии: были диагностированы хроническое воспаление легких и интерстициальная пневмония, однако формирования гранулем не было обнаружено. В итоге, только 2 из 3 макак, составляющих экспериментальную группу, были излечены [34]. Тем не менее результаты показывают, что данный аптамер обладает значительным потенциалом и может рассматриваться как основа для новых противотуберкулезных вакцин.…”
Section: аптамеры стимулирующие иммунный ответ к бактериямunclassified